Innovative and sustainable solutions for reducing ‘zero-dose’ vaccination: How can the region respond? - Abdel Majeed, Zeina; Ahmad, Nada; Mere, Osama; Farrukh, Saadia; Mohsni, Ezzeddine; Derow, Mohamed; Cuen, Adriana; Mohamed, Mona; Patni, Mohamedanas; Al Gunaid, Magid; Khader, Yousef; Al Nsour, Mohannad; et al. (Frontiers in Public Health, 2025)
BackgroundThis roundtable focused on the challenge of reaching zero-dose children in the Eastern Mediterranean Region (EMR) amid declining immunization rates and increasing health disparities. ‘Zero-dose’ children are concentrated in high-conflict or underserved areas, such as Pakistan, Afghanistan, Sudan, and Yemen, making them particularly vulnerable to vaccine-preventable diseases. This discussion convened key stakeholders, including public health experts, EPI managers, and representatives from organizations like WHO, Gavi, and CDC, to explore effective, sustainable solutions for reducing ‘zero-dose’ prevalence in the EMR.PurposeThe roundtable aimed to assess regional barriers to immunization, examine country-specific initiatives to reach ‘zero-dose’ children, and recommend targeted strategies that align with global immunization goals, such as the Immunization Agenda 2030.MethodThrough expert presentations, panel discussions, and participant interaction, attendees analyzed key causes of ‘zero-dose’ prevalence, focusing on conflict-related disruptions, health system fragility, and socioeconomic challenges. Comparative insights were drawn from other regions, highlighting adaptable solutions from Sub-Saharan Africa and other high-burden areas.ResultsFindings indicated that conflicts, infrastructure limitations, and social barriers are major drivers of low vaccination rates. Approximately 2.85 million ‘zero-dose’ children were identified in the EMR, primarily concentrated in a few high-burden countries. Country-specific efforts, such as the “Big Catch-Up” campaign, were acknowledged for their impact, but gaps in sustainable funding and operational capacity remain. Strategies focusing on community engagement, data-driven microplanning, and integration of immunization with broader health services were recommended to overcome access challenges.ConclusionTo reach ‘zero-dose’ children, coordinated, tailored approaches are essential. Community-driven microplanning and enhanced political and financial support can bolster immunization efforts in fragile settings. The roundtable underscored the role of primary health systems in addressing vaccination gaps, contributing to universal health coverage, and fostering resilience in conflict-affected areas. Future policies should prioritize collaboration among sectors, sustainable funding, and innovative outreach to achieve immunization equity across the EMR.